Aportes a la producción sustentable de soja mediante el mejoramiento genético de los rizobios - Liebrenz, Karen Ivana (2022)
Soybean is the most inoculant-consuming crop in the world, carrying strains belonging to the extremely related species Bradyrhizobium japonicum and Bradyrhizobium diazoefficiens. Currently, it is well known that B. japonicum has higher efficiency of soybean colonization than B. diazoefficiens, but the molecular mechanism underlying this differential symbiotic performance remains unclear. In the present doctoral thesis, genome resequencing of four spontaneous oxidative stress-resistant mutants derived from the commercial strain B. japonicum E109 combined with molecular and physiological studies allowed identifying an antioxidant cluster (BjAC) containing a transcriptional regulator (glxA) that controls the expression of a catalase (catA) and a phosphohydrolase (yfbR) related to the hydrolysis of hydrogen peroxide and oxidized nucleotides. Integrated synteny and phylogenetic analyses supported the fact that BjAC emergence in the B. japonicum lineage occurred after its divergence from the B. diazoefficiens lineage. The transformation of the model bacterium B. diazoefficiens USDA110 with BjAC from E109 significantly increased its ability to colonize soybean roots, experimentally recapitulating the beneficial effects of the occurrence of BjAC in B. japonicum. In addition, the glxA mutation increased the nodulation competitiveness and plant growth-promoting efficiency of E109.\nA variety of glyphosate resistance mechanisms, including target alteration and control of the uptake, export and degradation of glyphosate, has been reported in different organisms. However, the emergence of glyphosate resistance in rhizobia has not been studied at genetic level. In the present doctoral thesis, the genome resequencing of spontaneous glyphosate-resistant mutants derived from the soybean inoculant Bradyrhizobium japonicum E109 allowed identifying genes associated with the uptake (gltL and cya) and degradation (zigA and betA) of glyphosate as well as with nitrogen fixation (nifH). Mutations in gltL, cya, zigA, betA and nifH reduce the initial lag phase under glyphosate stress, supporting the contribution of these mutations to bypass the bacteriostatic effects of glyphosate. In addition to glyphosate resistance, mutation of the serine 90 phosphorylation site of NifH to alanine increased the citrate synthase activity, growth rate and plant growth-promoting efficiency of E109 in absence of glyphosate stress. These results suggest that this mutation contributes to mitigating the bacteriostatic action of glyphosate via an increased metabolic activity, and indicates that this phosphorylation plays roles during both the free-living and symbiotic growth stages of rhizobia. To our knowledge, this is the first report to describe a function of nitrogenase, in particular NifH, besides nitrogen fixation and a possible role of its phosphorylation site in the modulation of metabolism.\nFinally, the potential applications of these types of non-genetically modified mutant microbes (spontaneous oxidative stress-resistant and glyphosate-resistant mutants) in soybean production worldwide are discussed.